The Use of Haptic and Tactile Information in the Car to Improve Driving Safety: A Review of Current Technologies - Gaffary, Yoren; Lécuyer, Anatole (Frontiers in ICT, 2018)
This paper surveys the haptic technologies deployed in cars and their uses to enhance drivers' safety during manual driving. These technologies enable to deliver haptic (tactile or kinesthetic) feedback at various areas of the car, such as the steering wheel, the seat or the pedal. The paper explores two main uses of the haptic modality to fulfill the safety objective: to provide driving assistance and warning. Driving assistance concerns the transmission of information usually conveyed with other modalities for controlling the car's functions, maneuvering support and guidance. Warning concerns the prevention of accidents using emergency warnings, increasing the awareness of surroundings and preventing collisions, lane departures and speeding. This paper discusses how haptic feedback has been introduced so far for these purposes, and provides perspectives regarding the present and future of haptic cars meant to increase driver's safety.